Perencanaan Design Engine pada Mobil Minimalis Roda Tiga - Rezky Fardhan Fahrezy; George Endri Kusuma; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In every era development from time after time also followed with requirement developmentof transportation in society. Generally there are 2 kinds of land transportations that human mostlyhave, they are 2 wheel and 4 wheel transportations. While for complete the defeciency from that 2kinds of transpotation, then three wheel car concept created.Three wheel car have minimalist conceptthats mean comfortable and simple. With using tilting trike system which it make sure the easy accesfor any situation on the road which its need suitable engine spesification to support that concept.Because of that, this research is made to plan design engine that suitable with that concept by usingtorque and power manual calculation method, which it later tested by dynotest to look for the result ofengine performances on three wheel car.From torque and power calculation, its show minimumtorque requirements at 6500 rpm is 13,63 Nm and power requirements at 8500 rpm is 12,15 Hp. Thenthe result obtained Yamaha Scorpio Z 2007 engine that aplied on three wheel car which is tested byDynotest and show the result maximum torque at 5318 rpm is 22,90 Nm and maximum power at 8500rpm is 20,7 Hp.